Discovering Patterns of Urban Development in Skopje - Gievska, Sonja; Marina, Ognen; Ilievski, Ilija (Università degli Studi Roma Tre, 2014)
The goal of this research is to develop a tool that employs intelligent technologies to capture the patterns of urban change driven by a diverse set of context factors. Data mining provides opportunities and knowledge embedded in the urban structure, which complement and extend the data previously obtained with other approaches. A case study is in place to investigate the modeling and predictive capabilities of the tool. A number of simulations have revealed distinctive local patterns of urban change in the city of Skopje, shaped by local urban spatial and institutional structures. This study shows the possibilities of intelligent technologies in the interpretation of the historical evidence of urban development and better understanding of the urban phenomenon.
Keywords: Urban dynamics, urban transformation, knowledge-based approach, data mining